2013
DOI: 10.4103/0253-7613.121385
|View full text |Cite
|
Sign up to set email alerts
|

Pott′s disease and hypercalcemia in a patient with rheumatoid arthritis receiving methotrexate monotherapy

Abstract: Methotrexate (MTX) may have adverse effects on multiple organs and system. A few cases of pulmonary tuberculosis in-patients with rheumatoid arthritis (RA) while receiving MTX monotherapy has been reported in the literature. We submit a case of vertebral tuberculosis with hypercalcemia in a patient receiving MTX monotherapy. Patient with RA taking MTX for 15 years developed pancytopenia, skin necrosis, tuberculous spondylodiscitis and hypercalcemia. The present case showed adverse effects of MTX therapy may oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Reported experience on the use of IS agents 5.1 Traditional IS agents Current studies regarding this issue are mainly focused on biological therapy, although some studies have indicated the potential risk for developing a TB when using traditional IS agents, particularly MTX. Zorlu et al reported a clinical case of a 74-year-old female patient with RA controlled with MTX monotherapy during 10 years who unusually presented with spondylodiscitis, hypercalcemia, pancytopenia and skin necrosis [145]. In spite of its singularity, this case seems to share certain characteristics with previously reported cases [146] in that, as the authors indicate, there is a need for monitoring these potential complications in patients treated with MTX [145].…”
Section: In Patients With Hcv Infectionmentioning
confidence: 70%
See 1 more Smart Citation
“…Reported experience on the use of IS agents 5.1 Traditional IS agents Current studies regarding this issue are mainly focused on biological therapy, although some studies have indicated the potential risk for developing a TB when using traditional IS agents, particularly MTX. Zorlu et al reported a clinical case of a 74-year-old female patient with RA controlled with MTX monotherapy during 10 years who unusually presented with spondylodiscitis, hypercalcemia, pancytopenia and skin necrosis [145]. In spite of its singularity, this case seems to share certain characteristics with previously reported cases [146] in that, as the authors indicate, there is a need for monitoring these potential complications in patients treated with MTX [145].…”
Section: In Patients With Hcv Infectionmentioning
confidence: 70%
“…Zorlu et al reported a clinical case of a 74-year-old female patient with RA controlled with MTX monotherapy during 10 years who unusually presented with spondylodiscitis, hypercalcemia, pancytopenia and skin necrosis [145]. In spite of its singularity, this case seems to share certain characteristics with previously reported cases [146] in that, as the authors indicate, there is a need for monitoring these potential complications in patients treated with MTX [145]. Moreover, Chen et al reported the potential relationship between the use of these traditional IS agents for treatment of psoriasis (with or without associated arthritis) and developing of active TB [147].…”
Section: In Patients With Hcv Infectionmentioning
confidence: 99%
“…Meningoencephalitis. The treatment of RA patients with immunosuppressive drugs and DMARDS increases the susceptibility of opportunistic central nervous system infections [1,[44][45][46]. Symptoms of CNS infections have a wide range of presentation, such as fever, weight loss, focal neurological deficits, seizures, among others [1].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Many different agents were described in patients with RA, with especial attention for tuberculosis, neurolues, fungal and viral infections [44][45][46][47][48]. Patients taking TNF-α inhibitors and others biologic agents (such as infliximab, adalimumab, golimumab, etanercept and certolizumab) are at great risk for serious infections events such as tuberculosis and infections caused by opportunistic agents (histoplasmosis, coccidiodomycosis and Pneumocystis pneumonia are the most frequent agents) [49].…”
Section: Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation